2009
DOI: 10.1188/09.onf.353-361
|View full text |Cite
|
Sign up to set email alerts
|

Fatalism and Mammography in a Multicultural Population

Abstract: Purpose/Objectives: To assess levels of fatalistic beliefs and their association with mammography use in four population groups in Israel.Design: Telephone survey.Setting: Maccabi Healthcare Services in Israel.Sample: A random sample of 1,550 Arabic and Jewish women.Methods: A random telephone survey was performed during May and June 2007. Women's fatalistic beliefs were measured. Information from claims records regarding mammography use was obtained for each woman.Main Research Variables: Levels of fatalistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Some women may believe that death is inevitable when cancer is present (Baron-Epel et al, 2009b). This view is common among some women (Remmenick, 2006) and can act as a barrier to screening activities (Mayo et al, 2001;Petro-Nustas and Mikhail, 2002;Lamyian et al, 2007;Baron-Epel et al, 2009b;Azaiza et al, 2010). Fatalism has mostly been found in women of low socioeconomic status and educational levels, but has also been noted in affluent populations (Baron-Epel andKlin, 2009a Baron-Epel et al, 2009b;.…”
Section: Religious Influences Breast Cancer Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…Some women may believe that death is inevitable when cancer is present (Baron-Epel et al, 2009b). This view is common among some women (Remmenick, 2006) and can act as a barrier to screening activities (Mayo et al, 2001;Petro-Nustas and Mikhail, 2002;Lamyian et al, 2007;Baron-Epel et al, 2009b;Azaiza et al, 2010). Fatalism has mostly been found in women of low socioeconomic status and educational levels, but has also been noted in affluent populations (Baron-Epel andKlin, 2009a Baron-Epel et al, 2009b;.…”
Section: Religious Influences Breast Cancer Screeningmentioning
confidence: 99%
“…This passive behavior can arise from a belief that external forces are in control (Straughan and Seow as quoted by Baron-Epel et al, 2009b). Some women may believe that death is inevitable when cancer is present (Baron-Epel et al, 2009b). This view is common among some women (Remmenick, 2006) and can act as a barrier to screening activities (Mayo et al, 2001;Petro-Nustas and Mikhail, 2002;Lamyian et al, 2007;Baron-Epel et al, 2009b;Azaiza et al, 2010).…”
Section: Religious Influences Breast Cancer Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that increased risk perception and disease fear may not lead to the promotion of preventive behaviors (Consedine et al, 2004;Hay et al, 2006;Al-Naggar and Bobryshev, 2012) and in some cases result in conditions such as resistance or fatalism in the face of disease (Baron-Epel et al, 2009). The HBM ignores the social and environmental factors like social norms concerning the interactions between the individual and the environment, and focuses primarily on the role of intrapersonal individual (Glanz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A topic that is part of popular discourse but has received little formal attention is the role of fatalism in the risky road use behaviour in developing countries [5], although its role in other health areas has been studied. Some examples from other areas of health include a study of the influence of fatalism on mammography screening rates among four different populations in Israel [6], the extent of fatalism about human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) in Mali and its effect on prevention behaviours [7], general fatalism about cancer [8], the mediating role of fatalism in knowledge of HIV/AIDS among Native Americans [9], and the roles of fatalism, norms and social background in several health screening behaviours [10]. The few studies of fatalism in road safety in developing countries have been conducted in Africa [11][12][13][14] and have demonstrated the influence of both fatalism and superstition on beliefs about preventive behaviours.…”
Section: Introductionmentioning
confidence: 99%